Methodology Of Developing Student’s Writing Skills with The Assistance of Independent Learning (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
The article is devoted to the study of ways to develop selfeducation skills in English lessons at different stages of learning. The author gives a General description of each method and justifies their effectiveness